WPŁYW EWALUACJI WYBRANYCH KOMPETENCJI NA POPRAWNOŚĆ WYPOWIEDZI PISEMNEJ - Agnieszka Dryjańska (Neofilolog, 2019)
Writing is a complex skill since it requires the integration of various competences, which is a phenomenon extensively examined and discussed by researchers. However, the relation among these competences and their mutual influence, particularly at lower language proficiency levels (A1-A2/A2+), are analyzed more seldom. This issue constitutes the primary interest of our research. Carried out in the Institute of Romance Studies at Warsaw University, it focused on the following questions: how to adjust the evaluation method taking into account the above relation in order to facilitate the understanding of the complexity of the process of writing and to increase its effectiveness. The main study was preceded by a survey, conducted among all the students of the first year, who were beginners, concerning their perception of the difficulties of writing as well as their needs and expectations towards the writing class.